Tongue base reduction with radiofrequency tissue ablation: preliminary results after two treatment sessions - Stuck, Boris; Maurer, Joachim T.; Hörmann, Karl (Sleep and breathing, 2000)
Over the last few years, different surgical techniques for the treatment of obstructive sleep apnea syndrome have been developed. While new methods for the treatment of velopharyngeal obstruction turned out to be safe and effective, treatment of hypopharyngeal obstruction due to tongue base hypertrophy has remained, in many aspects, an unsolved problem. Surgical techniques for partial resection of the tongue base (midline glossectomy, lingualplasty) are effective but very invasive procedures requiring temporary tracheotomy, and have high postoperative morbidity. A maxillofacial approach showed significant reduction in the Respiratory Disturbance Index (RDI), especially when bimaxillar osteotomies are performed. Along with the concerns of postoperative morbidity, these techniques require general anesthesia and hospitalization.